The Position of Muslim Jurists on Aristotle’s Logic - Farhat, Ismail Salem ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
This study explores the diverse stances of Muslim jurists toward Aristotelian logic, highlighting the intellectual division it generated within Islamic thought. Scholars split into two main camps: those who embraced logic, such as Al-Ghazali and Ibn Hazm, and those who vehemently rejected it, including numerous theologians and jurists who deemed it alien to the spirit of Islamic law. The research emphasizes Al-Ghazali’s significant role in integrating logic into Islamic sciences, despite his rejection of parts of Greek metaphysics and natural philosophy. This integration marked a pivotal shift in Islamic intellectual history, dividing it into eras of rejection and acceptance of logic. The paper particularly focuses on Ibn Taymiyyah’s critical opposition to Aristotelian logic during the 13th century and compares the differing attitudes of jurists from the Eastern and Western Islamic worlds toward Al-Ghazali’s position.